Simulations of Mars Rover Traverses. Issue 1 (30th September 2013) - Zhou, Feng; Arvidson, Raymond E.; Bennett, Keith; Trease, Brian; Lindemann, Randel; Bellutta, Paolo; Iagnemma, Karl; Senatore, Carmine; Van, Michel; Wettergreen, David
<x xml:space="preserve">Abstract</x> Artemis (Adams‐based Rover Terramechanics and Mobility Interaction Simulator) is a software tool developed to simulate rigid‐wheel planetary rover traverses across natural terrain surfaces. It is based on mechanically realistic rover models and the use of classical terramechanics expressions to model spatially variable wheel‐soil and wheel‐bedrock properties. Artemis's capabilities and limitations for the Mars Exploration Rovers (Spirit and Opportunity) were explored using single‐wheel laboratory‐based tests, rover field tests at the Jet Propulsion Laboratory Mars Yard, and tests on bedrock and dune sand surfaces in the Mojave Desert. Artemis was then used to provide physical insight into the high soil sinkage and slippage encountered by Opportunity while crossing an aeolian ripple on the Meridiani plains and high motor currents encountered while driving on a tilted bedrock surface at Cape York on the rim of Endeavour Crater. Artemis will continue to evolve and is intended to be used on a continuing basis as a tool to help evaluate mobility issues over candidate Opportunity and the Mars Science Laboratory Curiosity rover drive paths, in addition to retrieval of terrain properties by the iterative registration of model and actual drive results.